Increased TRAb and/or Low Anti-TPO Titers at Diagnosis of Graves’ Disease are Associated with an Increased Risk of Developing Ophthalmopathy after Onset - Lantz, M.; Planck, T.; Åsman, P.; Hallengren, B. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Patients with low thyroid peroxidase antibodies (anti-TPO) and increased TSH-receptor antibodies (TRAb) at diagnosis of Graves’ disease (GD) have been suggested to have an increased risk to develop Graves’ ophthalmopathy (GO). The aim was to evaluate if GO development can be predicted.This is an observational study with registration of possible GD and GO risk factors.399 patients with GD were registered 2003–2008 in Malmö, Sweden and out of these 310 were retrospectively followed up to 6 years. The main outcome measures were anti-TPO titer, TRAb titer, smoking habits, radioiodine treatment and GO development.TRAb was assessed with a third generation assay at GD diagnosis in 231 patients. The proportion of patients with GO increased above the median 6.3 IU/L both at diagnosis of GD (p=0.001) and at follow-up (p=0.0001).The distribution of GO patients anti-TPO above or below 20 kIU/L at diagnosis of GD was similar between groups (p=0.239). However at follow-up anti-TPO<20 kIU/L was associated with an increased proportion of newly developed GO as compared to the cohort with anti-TPO>20 kIU/L (p=0.018).87% of patients who developed GO after GD diagnosis had TRAb above 6.3 IU/L and/or anti-TPO below 20 kIU/L. The proportion of GO was doubled in GD patients treated with radioiodine but could not explain the described findingsAnti-TPO<20 kIU/L and/or TRAb>6.3 IE/L at the time of GD diagnosis were associated with an increased risk to develop GO after diagnosis of GD.
Keywords: thyroid antibodies; ophthalmopathy; Graves’